(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objectives: Evaluation of outcomes and associated factors in walking rehabilitation using Body-Weight-Supported Treadmill Training (BWSTT) in patients with acute ischemic stroke. Subjects and methods: A prospective, interventional study comparing pre- and post-treatment outcomes over a 3-week period of walking rehabilitation using the BWSTT method in 71 inpatients with acute ischemic stroke at the Stroke Center, Phu Tho General Hospital. Results: The most common age group was > 65 years, with a male-to-female ratio of 1.45:1. Mild NIHSS scores accounted for 78.9%, and 95.8% of patients underwent BWSTT intervention within ≤ 7 days after stroke onset. After 3 weeks of BWSTT intervention, significant improvements were observed across all four scales: FAC, FMA-LE, BBS, and TUG (p < 0.05). Factors associated with walking rehabilitation outcomes included younger age (< 45 years), which showed better walking function improvement on the FAC scale compared to other age groups, and patients with lower NIHSS demonstrated better improvement in walking function on the FMA-LE scale compared to those with moderate NIHSS. Conclusion: BWSTT method improved in FAC, FMA-LE, BBS, and TUG scores in patient with acute ischemic stroke. Younger patients (< 45 years) showed better walking function improvement on the FAC scale, while patients with mild stroke revealed greater improvement on the FMA-LE scale compared to those with severe stroke.